The covenant of reason rationality and the commitments of thought - Levi, Isaac 1930-2018 (Cambridge Univ. Press, 1997)
Isaac Levi is one of the preeminent philosophers in the areas of pragmatic rationality and epistemology. This collection of essays constitutes an important presentation of his original and influential ideas about rational choice and belief. A wide range of topics is covered, including consequentialism and sequential choice, consensus, voluntarism of belief, and the tolerance of the opinions of others. This major collection will be eagerly sought out by a wide range of philosophers in epistemology, logic, ethics, and philosophy of science, as well as economists, decision theorists, and statisticians.
Keywords: Choix rationnels, Théorie des; Croyance et doute; Norme (Philosophie); Raison; Raisonnement; Rationaliteit; Rationele keuze; Belief and doubt; Norm (Philosophy); Rational choice theory; Reason; Reasoning; Vernunft; Rational Choice; Rationalität